Decreased Mucosal Sulfide Detoxification Is Related to an Impaired Butyrate Oxidation in Ulcerative Colitis - De Preter, Vicky; Arijs, Ingrid; Windey, Karen; Vanhove, Wiebe; Vermeire, Severine; Schuit, Frans; Rutgeerts, Paul; Verbeke, Kristin (Inflammatory bowel diseases, 2012)
Defective detoxification of sulfides leads to damage to the mucosa and may play a role in the etiology of ulcerative colitis (UC). The colonic mucosal thiosulfate sulfurtransferase (TST) enzyme removes H2S by conversion to the less toxic thiocyanate. In this study we measured colonic mucosal TST enzyme activity and gene expression in UC and controls. In addition, the influence of sulfides on butyrate oxidation was evaluated.MethodsColonic mucosal biopsies were collected from 92 UC patients and 24 controls. TST activity was measured spectrophotometrically. To assess gene expression, total RNA from biopsies was used for quantitative reverse-transcription polymerase chain reaction (RT-PCR). In 20 UC patients, gene expression was reassessed after their first treatment with infliximab. To evaluate the effect of sulfides on butyrate oxidation, biopsies were incubated with 1.5 mM NaHS.ResultsTST enzyme activity and gene expression were significantly decreased in UC patients vs. controls (P < 0.001). UC patients, classified into disease activity subgroups, showed a significantly decreased TST activity and gene expression in the subgroups as compared to healthy subjects (P < 0.05 for all). In 20 patients, gene expression was reassessed after their first infliximab therapy. In responders to infliximab, a significant increase in TST gene expression was observed. However, TST mRNA levels did not return to control values after therapy in the responders. In controls, but not in UC, sulfide significantly decreased butyrate oxidation.ConclusionsWe found an impaired detoxification mechanism of sulfide at TST protein and RNA level in UC. Inflammation was clearly associated with the observed TST deficiency.